Improved Dynamic Mechanical Properties of Modified PTFE Jet Penetrating Charge with Shell - Chang, B.H.; Yin, J.P.; Cui, Z.Q.; Liu, T.X. (Проблемы прочности, 2016)
A modified polytetrafluoroethylene (PTFE) was produced by the addition of copper powder to improve the mechanical properties and penetration performance of conventional PTFE. Static compression and split Hopkinson pressure bar test analyses verified the improved mechanical properties of the modified PTFE. Shaped charge structure was designed with by applying modified PTFE to liner material, the formation of modified PTFE jet and the process of jet penetrating shell charge were researched by numerical simulation. As compared to Teflon, results demonstrated that the mechanical properties of the modified PTFE have been significantly improved to achieve greater consistency of jet formation, stronger penetration, broadened pore size, and increased damage performance in the absence of a charge shell explosion.